2013
DOI: 10.1177/0193945913511154
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Staffing and Quality of Life in Western New York Nursing Homes

Abstract: This study investigated the relationship between nurse staffing and quality of life (QOL) in Western New York State nursing homes. This was a cross-sectional, correlational study. The independent variables were hours per resident day (HPRD), skill mix, and turnover rate of nursing staff. The outcomes were measured using the self-reported QOL instrument. No coefficients were statistically significant with registered nurses' (RNs) HPRD. Certified nursing assistant (CNA) HPRD had a statistically significant posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
2
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 31 publications
0
28
2
5
Order By: Relevance
“…In contrast, other researchers reported the quantity of nurse staffing was not statistically significant or did not contribute to resident outcomes (Johnson‐Pawlson & Infeld, ; Moseley & Jones, ; Rantz et al., ; Wan, ). Recent studies used quality of life (QOL) as the outcome variable with nursing staff, but the results varied and more research is needed (Shin, ; Shin, Park, & Huh, ).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, other researchers reported the quantity of nurse staffing was not statistically significant or did not contribute to resident outcomes (Johnson‐Pawlson & Infeld, ; Moseley & Jones, ; Rantz et al., ; Wan, ). Recent studies used quality of life (QOL) as the outcome variable with nursing staff, but the results varied and more research is needed (Shin, ; Shin, Park, & Huh, ).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…The skill mix studies that examined more licensed nursing hours (RN or LPN hours) versus unlicensed nursing hours (CNA hours) reported that more licensed hours positively influenced pressure ulcers, discharge to home, death, and functional ability (Bates‐Jensen et al., ; Bliesmer et al., ). A higher ratio of RNs to LPNs and CNAs had a statistically significant negative influence on some domains of QOL: meaningful activity, food enjoyment, and security (Shin et al., ).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…: age, education, chronical conditions) and facility characteristics (e.g. : facility size, nursing home sta ng rates) are signi cantly associated with QOL [7,9,11]. The study of Shippee et al (2015a) is one of the rst studies that subdivides QOL in different domains, in order to have a more nuanced understanding of how indicators are associated with QOL.…”
Section: Discussionmentioning
confidence: 99%
“…A study focusing on this topic concluded that QOL is affected by resident characteristics (age, gender, education or chronical conditions) and showed that physical disabilities, mental health problems, and age are negatively associated with the residents' QOL [7]. Besides resident characteristics, research has also proven that QOL is affected by facility characteristics like facility size [7,9], ownership type [10], nursing home sta ng rates [11] and nancial characteristics [7]. For instance: past research indicated that ownership type might explain QOL as residents in smaller and public nursing homes report better QOL [10].…”
Section: Introductionmentioning
confidence: 99%